2013
DOI: 10.1088/0004-637x/763/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Outer Galactic Halo With Rr Lyrae From the Catalina Surveys

Abstract: We present the analysis of 12227 type-ab RR Lyrae found among the 200 million public lightcurves in the Catalina Surveys Data Release 1 (CSDR1 1 ). These stars span the largest volume of the Milky Way ever surveyed with RR Lyrae, covering ∼ 20,000 square degrees of the sky (0 • < α < 360 • , −22 • < δ < 65 • ) to heliocentric distances of up to 60kpc. Each of the RR Lyrae are observed between 60 and 419 times over a six-year period. Using period finding and Fourier fitting techniques we determine periods and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
222
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(242 citation statements)
references
References 84 publications
14
222
2
1
Order By: Relevance
“…The percentage increase in the number of SSS RRab's identified in this work is similar to the increases in CSS-N RRab's from Drake et al (2013b) and DR14 compared to Drake et al (2013a). The combined number from CSS-N, MLS, and SSS data now total ∼33 000 RRab's (including previously known sources).…”
Section: Rrab'ssupporting
confidence: 78%
See 2 more Smart Citations
“…The percentage increase in the number of SSS RRab's identified in this work is similar to the increases in CSS-N RRab's from Drake et al (2013b) and DR14 compared to Drake et al (2013a). The combined number from CSS-N, MLS, and SSS data now total ∼33 000 RRab's (including previously known sources).…”
Section: Rrab'ssupporting
confidence: 78%
“…We note that our value of M t is as used by Drake et al (2013a) and is based on the fit to the light curve rather than sum of the values for the data points. The M t parameter itself is a measure of the fraction of time that a variable is below the mean magnitude compared to above it.…”
Section: Parameter and Class Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data are automatically processed in real time, and optical transients are immediately distributed using a variety of electronic mechanisms. 3 The data are unfiltered but are broadly calibrated to Johnson V from 2MASS data (see Drake et al 2013 for details). The accuracy of the V-band photometry is highly dependent on source colour but comparison with Landolt standard stars has shown that the colour correction is small for blue objects.…”
Section: Catalina Real-time Transient Surveymentioning
confidence: 99%
“…The images are processed using an aperture photometry pipeline based on SEXTRACTOR (Bertin & Arnouts 1996) and the unfiltered magnitudes are transformed to Landolt V using observations of standard stars (Drake et al 2013). Information on the transients detected, e.g.…”
Section: V L I G H T C U Rv E S F Ro M C Rt Smentioning
confidence: 99%